Timing of mass spawning in corals: potential influence of the coincidence of lunar factors and associated changes in atmospheric pressure from northern and southern hemisphere case studies. Issue 2 (3rd April 2018) - Wolstenholme, Jacqueline; Nozawa, Yoko; Byrne, Maria; Burke, William
Abstract: Synchronised multispecies mass spawning events are striking features of reproduction in corals. This synchronous gamete release of thousands of animals over vast stretches of reef is thought to be cued by rhythms of the Moon. However, the mechanisms are not fully understood. We propose an explanation that may contribute to understanding this mechanism, that spawning is triggered by the coincidence of two factors, each in different lunar rhythms. We investigate this proposal in case studies using seven years of coral spawning data from two locations: Kochi, Japan and Lizard Island, Australia. Our calculations show that a feature in a lunar synodic rhythm (the third quarter) will synchronise with a feature in a lunar non-synodic rhythm (the zero declination) usually once, although occasionally twice in a year. Supported by data on the date of spawning from the two locations, we suggest that this coincidence of lunar factors exerts an important influence on the timing of annual mass spawning in corals. This coincidence may be associated with low atmospheric pressure. Spawning at the time of the third lunar quarter may favour fertilisation success due to the reduced currents during neap tides associated with the lower gravitational pressure of the lunar quarters.